Project-based carbon trading: A flexible mechanism to promote trans-regional cooperation - LIAO Zhenliang*; SHEN Yifan; YAO Qiang (能源环境保护)
The industry baseline method is adopted to allocate carbon allowances in China's national carbon market, neither considering its huge inner regional disparity, nor exhibiting enough flexibility to promote renewable energy. The origination, development and regional imbalance were discussed, and a project-based carbon trading of trans-regional cooperation mechanism was proposed under the direction of theories of carbon trading, trans-regional coordination and ecological compensation. In the proposed mechanism, allowance re-allocation is suggested under the principle of responsibility sharing between producing and consuming areas, and the reduction volume produced through the trans-regional investment projects can be allowed to offset the investor′s carbon allowance compliance. Based on the analysis, we pointed out that this flexible mechanism could help achieve a win-win situation between Eastern and Central & Western China. Suggestions to establish the mechanism were given, including the methodology probing, the institutional designing, and the pilot-program raising.